A Case Report on Congenital Ichthyosis - Collodion Baby - Hassan, Md Kamrul; Saha, Aloke Kumar; Begum, Poly; Akter, Tahmina; Saha, Shyamol Kumar (Faridpur Medical College Journal, 2016)
Collodion baby describes a highly characteristic clinical entity in newborns encased in a yellowish translucent membrane resembling collodion. In most cases the condition either precedes the development of one of a variety of ichthyoses, the commonest of which are lamellar ichthyosis and non-bullous ichthyosiform erythroderma, or occasionally represents an initial phase of other ichthyoses such as ichthyosis vulgaris. In at least 10% of all cases of collodion baby, the condition is followed by a mild ichthyosis of lamellar type, so mild as to be considered more or less normal, so-called self-healing collodion baby or 'lamellar ichthyosis of the newborn'. In this report, we present a severe form of ichthyosis. Faridpur Med. Coll. J. Jan 2016;11(1): 39-42